Diasporic histories cultural archives of Chinese transnationalism - Riemenschnitter, Andrea; Madsen, Deborah L. (Hong Kong University Press ; Eurospan, distributor], 2009)
This work engages cultural representations of the subjectivities and loyalties of Chinese migrant communities, including analyses of aesthetic texts, as well as theoretical approaches in cultural studies.